2012
DOI: 10.4084/mjhid.2012.001
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Effect of the −158 Gγ (C→t) XMN-1 Polymorphism in Indian Sickle Cell Patients

Abstract: Xmn1 polymorphism is a known factor, which increases fetal haemoglobin production. Among the inherited disorders of blood, thalassaemia and Sickle Cell Diseases contributes to a major bulk of genetic diseases in India. Our aim was to verify the role of the Xmn1 polymorphism as a modulating factor in sickle cell patients and frequency of the polymorphism in Indian sickle cell patients. 60 sickle homozygous and 75 sickle beta thalassemia patients were included and 5 ml blood sample was collected from them. Scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
1
8
1
Order By: Relevance
“…These findings could be explained by the inhibitory effect of HbF on deoxy‐HbS polymerization (which in turn is the major driver of the pathophysiology of this disease) . These observations were to a great extent similar to those reported in Indian SCD patients, where it was found that carriers of the minor allele of rs7482144 had a milder disease with higher hemoglobin and HbF, and lower transfusion and pain crises frequencies . Moreover, Sheehan et al demonstrated that minor alleles at rs1427407 were associated with higher Hb and lower pain frequencies compared to noncarriers.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…These findings could be explained by the inhibitory effect of HbF on deoxy‐HbS polymerization (which in turn is the major driver of the pathophysiology of this disease) . These observations were to a great extent similar to those reported in Indian SCD patients, where it was found that carriers of the minor allele of rs7482144 had a milder disease with higher hemoglobin and HbF, and lower transfusion and pain crises frequencies . Moreover, Sheehan et al demonstrated that minor alleles at rs1427407 were associated with higher Hb and lower pain frequencies compared to noncarriers.…”
Section: Discussionsupporting
confidence: 69%
“…35 These observations were to a great extent similar to those reported in Indian SCD patients, where it was found that carriers of the minor allele of rs7482144 had a milder disease with higher hemoglobin and HbF, and lower transfusion and pain crises frequencies. 36,37 Moreover, Sheehan et al 38 demonstrated that minor alleles at rs1427407 were associated with higher Hb and lower pain frequencies compared to noncarriers. While Lettre et al 15 failed to find a significant association between pain episodes frequencies and individual SNP that they studied (including rs7482144 and rs9399137), they did find an inverse correlation between HbF and pain frequency.…”
Section: Americans and Is Intermediate Between The Lower Rates Repormentioning
confidence: 99%
“…It has been initially suggested that haplotypes in the HBB gene cluster possibly affect the possibly the clinical response to HU, likely mediated by their genetically-determined effect on HbF level [34,72,73] (Table 1). There is a positive association between the XmnI polymorphism (rs7482144) in the γ-globin promoter and HbF levels in numerous populations [15,16,7476], as well as accounting for more than 2% in HbF variation in patients and 13 – 32% in F cell variation in non-anaemic European population [77]. This polymorphism has also been associated with the less severe disease course of patients with Senegal and/or Indian-Arab haplotype backgrounds as well as improved response to HU treatment [74,75,7781].…”
Section: Resultsmentioning
confidence: 99%
“…There is a positive association between the XmnI polymorphism (rs7482144) in the γ-globin promoter and HbF levels in numerous populations [15,16,7476], as well as accounting for more than 2% in HbF variation in patients and 13 – 32% in F cell variation in non-anaemic European population [77]. This polymorphism has also been associated with the less severe disease course of patients with Senegal and/or Indian-Arab haplotype backgrounds as well as improved response to HU treatment [74,75,7781]. Subsequent research provides some evidence that the effect of HU on HbF level could act on other HbF-promoting loci like BCL11A [26].…”
Section: Resultsmentioning
confidence: 99%
“…Each haplotype is associated with a characteristic average level of HbF (Arab-Indian>Senegal>Benin>Bantu); however, HbF levels varied among patients homozygous for any haplotype. For example, in carriers of Senegal and Saudi-Indian haplotypes, Xmn1 CT restriction site polymorphism (158 bps upstream of HBG2 ) is associated with high HbF and Gγ-globin (HBG2) levels (Green et al , 1993; Chang et al , 1995; Pandey et al , 2012).…”
Section: Importance Of Hbf In Pathophysiology Of Scdmentioning
confidence: 99%